2021
DOI: 10.1091/mbc.e20-09-0585
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative and semiautomated method for determining misaligned and lagging chromosomes during mitosis

Abstract: Accurate chromosome alignment at metaphase facilitates the equal segregation of sister chromatids to each of the nascent daughter cells. Lack of proper metaphase alignment is an indicator of defective chromosome congression and aberrant kinetochore-microtubule attachments which in turn promotes chromosome missegregation and aneuploidy, hallmarks of cancer. Tools to sensitively, accurately and quantitatively measure chromosome alignment at metaphase will facilitate understanding of the contribution of chromosom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This is particularly imprecise when using chromosome labels, since the position of bulky chromosome arms do not always represent the position of kinetochores where microtubules attach to segregate them. Recent efforts to quantify lagging chromosomes from fixed cell analyses are an important step forward 60 . However, these approaches do not use a time-series, and therefore cannot capture the temporal and spatial evolution of short-lived events.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly imprecise when using chromosome labels, since the position of bulky chromosome arms do not always represent the position of kinetochores where microtubules attach to segregate them. Recent efforts to quantify lagging chromosomes from fixed cell analyses are an important step forward 60 . However, these approaches do not use a time-series, and therefore cannot capture the temporal and spatial evolution of short-lived events.…”
Section: Discussionmentioning
confidence: 99%
“…To test for alignment, we treated control and TEM4 depleted cells with the Eg5 inhibitor S-Trityl-L-Cysteine (STLC) to disrupt the formation of bipolar spindles. Cells were then released into media containing the proteasome inhibitor MG132 to allow for bipolar spindle formation and alignment, and kinetochore positions relative to the metaphase plate were monitored as previously reported (Gama Braga et al, 2021). We found that cells depleted of TEM4 exhibited a significant increase in misaligned kinetochores compared to control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Angular histograms were plotted using a custom R script (Scarpa et al, 2018). Misaligned and lagging chromosomes were quantified in fixed cells as previously described (Gama Braga et al, 2021). Briefly, spindle pole position was defined, followed by the establishment of an alignment region after equally dividing the area in between the poles of the cell into 5 zones.…”
Section: Image Quantification and Statistical Analysismentioning
confidence: 99%
“…To classify cells with misaligned chromosome, an automated analysis was employed as described previously ( Gama Braga et al., 2021 ). The standard/control used were the cells arrested at metaphase, and the distance between the two spindle poles in the control cells was accurately measured.…”
Section: Methodsmentioning
confidence: 99%